OXIDATION KINETIC OF TERNERY ZR-2.5%NB-Y ALLOYS AND RESISTANCE OF OXIDE SCALE AGAINST HYDROGEN PENETRATION AT HIGH TEMPERATURE - Hadi Prajitno, Djoko
Zirconium alloys identified as zircalloys 1,2,3, 4, and Zr-2,5%Nb are the component structure materials used in the nuclear power reactors such as fuel claddings, fuel channels, etc. Interests for zircalloys result from the low neutron absorption cross section of zirconium, the high mechanical strength and the good corrosion resistance at 350-380oC. For long term rector operation, component reactor underwent aging. Aging critical component reactor caused reduces life time service. Critical component reactor including: fuel cladding, coolant channel and pressure tube where the component of reactor is made from zircalloy. Aging mechanism of critical component reactor is PCI ( Pellet Cladding Interaction ), WSCI ( Waterside cladding interaction ), LOCA ( Loss of Cooling Accident ), HID (hydrogen induced damage) and Radiation damage. For long time service, zirconium alloy is limited by problem from hydrogen embrittlement and creep, and oxidation. It is obvious that further significant improvement in hydrogen embrittlement, creep and corrosion resistance requires development a new alloy. Addition yttrium to Zr-2,5%Nb alloy will improved oxidation resistance and hydrogen embrittlement of the alloy. Synthesis ternary alloy Zr-2,5%Nb-Y have been done at different yttrium content (0,5, 1, and 1,5). Single arc melting furnace is used for smelting of the Zr- 2,5%Nb-Y alloys. After smelting the alloys Zr-2,5%Nb-Y is heat treated at 900oC for 4 hours and quenched in water. After that the alloy underwent mechanical treatment by hot roll at 900oC with reduction of 30%. After hot roll the alloy is oxidized and hydrogen charging at high temperature. Addition yttrium to Zr- 2,5%Nb improved high temperature oxidation behavior due to formation of Y2O3 as a results weight gain during oxidation decreasing with temperature and time. The parabolic rate constant value of Zr-2,5%Nb alloy more higher compared with the alloy with yttrium addition. For Zr-2,5%Nb was 0,0002 at 600oC and 0.1624 at 800oC. For Zr-2,5%Nb-0,5%Y alloy was 0.00001 and 0.0838 respectively at 600oC and 800oC. Diffusion coefficient oxygen (D) in the oxide scale for Zr- 2,5%Nb alloy was 3x10-7 cm2/s at 800oC and more higher compare with Zrv 2,5%Nb-1,5Y alloy was 7x10-8 cm2/s. Addition Y on Zr-2,5%Nb alloy reduce activation energy formation with value 5.7 Kj/mol due to formation oxide scale Y2O3. Yttrium addition to Zr-2,5%Nb improved hydrogen penetration with decreasing ? phase of hydride on the surface alloy. From the x-ray diffraction data the value of ? phase on Zr-2,5%Nb was 32,53% and 25,42% and 11,55% respectively for Zr-2,5%Nb-0,5%Y and Zr-2,5%Nb-1,5%Y alloys. Formation Y2O3 on the oxide scale for Zr-2,5%Nb-Y alloy improve oxide scale against hydrogen penetration. X ray diffraction data and microstructure showed that there is no hydride appeared under oxide scale but for Zr-2,5%Nb alloy ? phase of appeared under oxide scale hydride. Promovendus was success to synthesized novelty Zr-2,5%Nb-Y alloy which is resistance to oxidation and hydrogen penetration for Zr-2,5%Nb-Y alloy and oxide scale formed on Zr-2,5%Nb-Y alloy. The new data of parabolic rate constant, diffusivity of oxygen in the oxide scale are main contribution of my research for sciences